The gender gap in STEM: (Female) teenagers' ICT skills and subsequent career paths - Friederike Hertweck; Judith Lehner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Skills shortage in the fields of Sciences, Technology, Engineering, and Mathematics (STEM) poses a significant challenge for industries globally. This study examines the interrelationship between high school students' gender, their proficiency in Information and Communication Technology (ICT), and their career preferences in the STEM domain. Based on representative data for German teenagers, our study shows that female adolescents are less likely to choose a career in STEM unless they have strong ICT skills in secondary school. The relationship does not hold for male students. Our findings can be explained with evidence that teenagers sort into occupations they believe to be good at and that female teenagers rather underestimate their true potential. Using different empirical approaches, we also show that ICT skills act as a moderator and not as a mediator in the gender-specific choice of training upon graduating from secondary school. – – Der Fachkräftemangel in den Bereichen Naturwissenschaften, Technik, Ingenieurwesen und Mathematik (MINT) stellt für die Industrie weltweit eine große Herausforderung dar. Diese Studie untersucht die Wechselbeziehung zwischen dem Geschlecht von Schülern, ihren Kenntnissen in der Informations- und Kommunikationstechnologie (ICT) und ihren Berufswünschen im MINT-Bereich. Basierend auf repräsentativen Daten deutscher Jugendlicher zeigt die Studie, dass weibliche Jugendliche weniger wahrscheinlich eine Karriere im MINT-Bereich wählen, wenn sie während der Mittelstufe keine guten ICT-Kenntnisse haben. Dieser Zusammenhang gilt nicht für männliche Schüler. Unsere Ergebnisse lassen sich damit erklären, dass Jugendliche sich für Berufe entscheiden, von denen sie glauben, dass sie gut darin sind, und dass weibliche Jugendliche ihr wahres Potenzial eher unterschätzen. Unter Verwendung verschiedener empirischer Ansätze zeigen wir auch, dass ICT-Kenntnisse als Moderator und nicht als Mediator bei der geschlechtsspezifischen Wahl der Ausbildung nach dem Schulabschluss wirken.
Keywords: I20; J24; J08; 330; Career choice; ICT skills; digital literacy; gender gap; STEM